2003
DOI: 10.1007/s10350-004-6543-z
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Rubber Band Ligation vs. Stapled Hemorrhoidectomy for Prolapsed Piles

Abstract: Stapled hemorrhoidectomy is associated with more pain and minor morbidity than rubber band ligation in the treatment of Grade III and small Grade IV piles. However, for those patients who do not want the risk of further intervention procedures, stapled hemorrhoidectomy offers the better chance of a symptomatic cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
63
0
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 25 publications
(31 reference statements)
4
63
0
8
Order By: Relevance
“…Postoperative bleeding was the most commonly reported complication; however, these rates were lower when compared with other methods of hemorrhoidectomy. 47,56 Bleeding following stapled hemorrhoidopexy is said to most commonly occur immediately after surgery or from day 7 onwards. It has been suggested that bleeding often occurs secondary to an arteriolar bleed along the staple line, from defective techniques that result in injury to the mucosa and may also be secondary to inflammation and/or rejection of the staples when the procedure is completed during a period of anusitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Postoperative bleeding was the most commonly reported complication; however, these rates were lower when compared with other methods of hemorrhoidectomy. 47,56 Bleeding following stapled hemorrhoidopexy is said to most commonly occur immediately after surgery or from day 7 onwards. It has been suggested that bleeding often occurs secondary to an arteriolar bleed along the staple line, from defective techniques that result in injury to the mucosa and may also be secondary to inflammation and/or rejection of the staples when the procedure is completed during a period of anusitis.…”
Section: Discussionmentioning
confidence: 99%
“…5,54,55 The judicious careful use of an Eisenhammer retractor for purse string suture insertion has been shown to reduce the incidence of these complications. 56,57 Soiling and mucus discharge was also documented. 4,9,30,32,46 Fecal urgency was also noted with an incidence range of 0.2 to 25% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Now it is the procedure of choice for patients who did not respond to office-based procedures or who unable to tolerate these procedures, grade three or four hemorrhoids, or patients with substantial external skin tags (5). Rubber band ligation is also widely used because it is a safe and effective method, involves less postoperative pain, and causes a quick recovery (9,(11)(12)(13). Complications are mostly minor.…”
Section: Discussionmentioning
confidence: 99%